Assessment of information as regards the toxicity of fumonisins for pigs, poultry and horses. (24th August 2022) - ,; Schrenk, Dieter; Bignami, Margherita; Bodin, Laurent; Chipman, James Kevin; del Mazo, Jesús; Grasl‐Kraupp, Bettina; Hogstrand, Christer; Leblanc, Jean‐Charles; Nielsen, Elsa; Ntzani, Evangelia; Petersen, Annette; et al.
Abstract: In 2018, the EFSA Panel on Contaminants in the Food Chain (CONTAM) adopted a Scientific Opinion on the risks for animal health related to the presence of fumonisins, their modified forms and hidden forms in feed. A no observed adverse effect level (NOAEL) of 1 mg/kg feed was established for pigs. In poultry a NOAEL of 20 mg/kg feed and in horses a reference point for adverse animal health effect of 8.8 mg/kg feed was established, referred to as NOAEL. The European Commission (EC) requested EFSA to review the information regarding the toxicity of fumonisins for pigs, poultry and horses and to revise, if necessary, the established NOAELs. The EFSA CONTAM Panel considered that the term reference point (RP) for adverse animal health effects better reflects the uncertainties in the available studies. New evidence which had become available since the previous opinion allowed to revise an RP for adverse animal health effects for poultry from 20 mg/kg to 1 mg/kg feed (based on a LOAEL of 2.5 mg/kg feed for reduced intestinal crypt depth) and for horses from 8.8 to 1.0 mg/kg feed (based on case studies on equine leukoencephalomalacia (ELEM)). For pigs, the previously established NOAEL was confirmed as no further studies suitable for deriving an RP for adverse animal health effects could be identified. Based on exposure estimates performed in the previous opinion, the risk of adverse health effects of feeds containing FB1–3 was considered a concern for poultry, when taking into account the RP of 1 mg/kg feed for intestinal effects. For horses and other solipeds, the risk is considered low, although a large uncertainty associated with exposure was identified. The same conclusions apply to the sum of FB1–3 and their hidden forms.